THE ROLE OF INTEREST GROUPS IN SHAPING OF PUBLIC POLICY A CASE STUDY OF AFGHANISTAN IN A YEAR BETWEEN 2014 AND 2021 - Sayed Israr Samim; Rasheedullah Shinwari; Ziauddin Gawhar (Policy Research Journal, 2025)
The paper examine the role of interest groups in shaping of public policies between the years 2014- 2021. It focuses to understand the structures involved in the process of public policy formulations in Afghanistan. The paper also explore the challenges these groups were facing between 2014 and 2021 while imposing on their interest in public policy making process. This research also explore the strategies taken be the interest groups while influencing the process of policy formulation. Mixed research Method was used to collect the data. 20 interviews with politician, civil society member, Journalist, social activists and academia were conducted and 30 questionnaires in the shape google form were shared with these categories of people. The findings of the research shows that between 2014 and 2021 various interest groups were involving in the process of policy formulation. These group were using different strategies to emphasize on their goals and objectives to be given attention while making policies. The groups were also faced by some challenges when they were trying to have an eye on the policy formulation process. Furthermore it reveal that people supports the interest group intervention in the public policies formulating process which can restrict the structures to the public interest. Finally the research has a light that these people were very aware of the role of the interest groups and see it as a positive initiative taken and implemented in this specific era of time.